Turkish-Iranian Relations in the Middle East: in Search of the Regional Balance - I. A. Svistunova (Vestnik MGIMO-Universiteta)
Turkey and Iran are two Middle Eastern neighbors building their relationship on the basis of competition and cooperation. Both countries aim at the position of regional leader and want to offer their own «model» of development to the Middle East. Historical neighborship has provided Turkey and Iran not only with the experience of struggle for influence, but an ability to interact in the spheres of overlapping interests as well. Turmoil in the Middle East attracts the attention of researchers to the issue of Turkish-Iranian relations. The article deals with the key areas of regional relations of the two countries reflecting their efforts to keep the power balance though they have contradicting interest. Islamic revolution in Iran in 1979 has put Turkish and Iranian «models» in adversary positions to one another emphasizing religion vs secularism.The Turkish side has broadened the range of its instruments after Justice and Development Party coming to power in Ankara, although its aim remains to be the promotion of Western concepts in the Middle East. The Party’s strategy to expand Turkish influence in the region takes into account the Ottoman heritage, which modern Ankara seeks to popularize in order to reinforce its claims to regional leadership. The competitive arsenal of the Turkish leadership includes historical ties with the peoples of the region and the experience of the Europeanization of the Muslim state.Iran is promoting its vision of Muslim democracy, positioning itself as a staunch fighter against the expansionism of the West and, despite the decline in warlike rhetoric, does not refuse to export the values of the Islamic revolution. Ankara is at odds with Western countries on private issues or methods, but generally it shares the same strategic approaches. Tehran, on the contrary, rejects the ideological rapprochement with the West and the borrowing of Western development models, advocating maintaining its own path. In fact, Iran and Turkey offer Middle Eastern countries alternative political transformation options.Iraq and Syria represent both the sphere of Turkish-Iranian competition and the possibility for tactical alignment on the basis of converging interests. The events of recent years have demonstrated that at the times when the Turkey and Iran sense common threats, they put their contradictions on the back burner. Pragmatism and rivalry in Turkish-Iranian relations are not alternatives but exist in parallel as a way of maintaining a regional balance of power between the two countries. This explains the ability of Ankara and Tehran to seek compromises. At the same time, the various approaches of these states to the future structure of the Middle East region will continue to hinder the creation of a stable alliance between them. These realities must be taken into account when assessing the prospects for the development of the regional situation and the potential of Turkish-Iranian relations, the study of which is especially important for Russia, taking into account trilateral cooperation to resolve the crisis in Syria.